Le Sabre de Lumière et de Vertu de Sagesse: Anatomie d'Une Rémémoration - Labrie, Vivian (Ethnologies, 1979)
AbstractThis paper describes how a very gifted acadian tale-teller, Hilaire Benoit, has proceeded from complete oblivion (forgetfulness?) to full recovery of one spécifie taie, Le sabre de lumière et de vertu de sagesse [The saber of light and wisdom). This taie belongs to the Irish tradition and it has also been found in a few samples in the French-Canadian tradition. It has been given number 305 A in Luc Lacourcière's fortheoming Catalogue raisonné du conte populaire français en Amérique du Nord. It is typical of the "story in the story" narrative form. It was possible to follow closely Hilaire's remembering through field notes and from some tape-recorded sessions. This progression is described here and it is followed by an analysis of the teller's mnemonic strategies which include: imagery of some key-motives, reiteration of segments where memory faits, detailed narration of well known segments, use of logic reconstruction, making of hypothesis, association with similar taies, association with the person from whom the tale was learned, endless repetition of mental work, questioning a person who knows the tale. To aid in comprehension of the argument, and for the sake of its own aesthetic quality, a full transcription of the final version is also given at the end of the discussion.